Textbook of family medicine - Rakel, Robert E.; Rakel, David (Elsevier Saunders, 2011)
Offers guidance on the principles of family medicine, primary care in the community, and various aspects of clinical practice. Suitable for both residents and practicing physicians, this title includes evidence-based, practical information to optimize your patient care and prepare you for the ABFM exam.